Survey efficiency of Metarhizium anisopliae and some insecticides against fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) under laboratory and net house conditions : - Zin, Mi Mi (Can Tho University, 2020)
In the experiment to evaluate the toxicity of four Metarhizium anisopliae (Ma) strains on FAW, the results showed that Ma S. frugiperda had the highest efficacy with 63.22% and no statistical difference with Ma N. lugen with 59.54%. The treatment of Naxa 800DP had the lowest efficacy with 35.46% at 7 days after dipping under laboratory conditions. Efficiency of seven spore concentrations from 106 to 109 spores/ml of Ma S. frugiperda were evaluted to FAW. All the result showed the treatments of Ma_109, Ma_5 ×108, Ma_108 spores/ml were high efficacy and no signification difference ach other with 75.92%, 74.67% and 73.42% respectively. The treatments of Ma_5 × 106 and Ma_106 were lower efficacy with 59.54 % and 58.16% at 7 days after dipping under laboratory conditions.